Media Framing of Children's Rights, Discrimination, and Prevention Efforts in the Educational Environment - Prasetyo Adinugroho Adi (Journal of Education and Teaching Learning, 2026)
Children's rights are fundamental human rights that must be protected. However, violations in the form of bullying and discrimination within educational environments remain a serious problem in Indonesia. This study analyzes media framing of children's rights issues, discrimination, and bullying prevention efforts in Indonesian educational settings using a qualitative descriptive case study approach and Entman’s (1993) framing model. Primary data from national media outlets (Kompas, Saibumi, MetroTVNews, Liputan6, RRI, and Alodokter) covering the period of August to November 2025 show a significant increase in bullying cases, from 285 cases in 2023 to 573 cases in 2024. Physical bullying dominated (55.5%), followed by verbal bullying (29.3%), with cyberbullying also rising sharply by 100%. The media define bullying as a violation of children's rights to protection and a safe education. They diagnose its causes as the lack of school supervision, tolerant norms toward discrimination (based on gender, socio-economic status, and identity), and the influence of social media. In moral judgments, the media portray victims as the vulnerable party and institutions such as KPAI and Komnas PA as defenders of children's rights, while schools and parents are viewed as ethically failing. The recommended solutions include holistic prevention through inclusive curricula, teacher training, psychological support, and child-friendly policies in line with the Convention on the Rights of the Child (CRC) and Law No. 35 of 2014. This framing influences public opinion and policy responses toward creating a discrimination-free educational environment.